(untitled) (Revista Contexto & Educação, 2024)
The analyzes in this article focus on the educational processes in Guinea-Bissau during the armed revolution, studying the main characteristics, data and statistics of colonial education imposed by the Portuguese and Amílcar Cabral’s criticisms of the assimilationist educational regime that reinforced the continuity of domination and submission. Identifying the national restructuring project proposed by PAIGC, the study addresses Paulo Freire’s arrival in Guinea-Bissau, invited by the country’s ministry of education and his political-educational praxis in the face of the complexities of the new nation. We propose a critical dialogue with the State machine, represented here by the leaders of PAIGC and its most significant decision: the adoption of the Portuguese language in the process of re-Africanization of mentalities, through the revolutionary education that would be developed in the country, as it has the Freire’s dilemma: how to exercise a liberating pedagogy and the complete emancipation of minds, teaching literacy with the colonizer’s language?